Effect in white shrimp Litopenaeus vannamei of Eleutherine bulbosa (Mill.) Urb. Powder on immune genes expression and resistance against Vibrio parahaemolyticus infection. Issue 102 (July 2020) - Munaeni, Waode; Widanarni,; Yuhana, Munti; Setiawati, Mia; Wahyudi, Aris Tri
Abstract: This study investigated the influence of Eleutherine bulbosa (Mill.) Urb. on the immune responses, bacterial population in the intestines, and resistance of white shrimp, Litopenaeus vannamei, against infection with Vibrio parahaemolyticus. Shrimp were fed with three dosages of powder, at 6.25 g kg–1 (P6.25), 12.5 g kg–1 (P12.5), and 25 g kg–1 (P25). One dosage of the crude extract was provided, 1.25 g kg–1 (E1.25), and the controls without administration of E. bulbosa consisted of a positive control (PC) and a negative control (NC). Feed supplementation was carried out for 30 days; then shrimp from all treatments were challenged by intramuscular injection with V. parahaemolyticus (10 6 cfu/mL), except for the NC. The results showed that supplementation with the powder and extract of E. bulbosa for 30 days resulted in significantly higher (P < 0.05) immune responses (total hemocyte count (THC), phenoloxidase activity (PO), respiratory bursts (RBs)), gene expression (prophenoloxidase (proPO), lipopolysaccharide- and β-1, 3-glucan-binding protein (LGBP)), and total bacterial count (TBC) compared to PC/NC. In post challenge testing, there were significantly higher levels for THC, PO, RBs, proPO, LGBP, and PE (peroxinetin), and the treatments were able to suppress V. parahaemolyticus in the intestines, hepatopancreas, and muscles and to reduce damage to the muscles and hepatopancreas. The survival rate with P12.5 was significantly higher compared to the other treatments. It was concluded that the shrimp receiving supplementation with the powder and extract of E. bulbosa had increased immunity and resistance against V. parahaemolyticus infection, with the best dosage being the P12.5 treatment. Highlights: The supplementation of E. bulbosa increased immunity and resistance against V. parahaemolyticus infection, with P12.5 showed the best dosage. The administration of the E. bulbosa powder or extract suppressed the V. parahaemolyticus population thus reducing damage to the muscle and hepatopancreas. Supplementation of E. bulbosa powder P12.5 gave better results than the extract dosage E1.25.